Analisis Pengaruh Inovasi Kemajuan Teknologi Pada Smartphone Terhadap Jumlah Penjualan Produk Handphone - Adnan Tariq; Bassam Raza (Jurnal Teknik dan Teknologi Indonesia, 2023)
. As for the procedures for buying piled up land, consumers must first buy a D.O (Dilevery Order) card at the cashier according to the size of the fleet being brought (large or small) then process the payment, then the fleet enters the loading process queue, then the D.O card is given to the operator excavator for loading piled up soil into the fleet tank, after the loading process is complete the fleet leaves. After receiving payment money from consumers, the cashier records sales transactions in the sales transaction book and then re-records the administration section into the master book for reports on the production of sales results which will be given to the person in charge. As long as the sales data management system is still recorded manually by the administration into the ledger, this risks causing delays in the preparation of reports because all sales transactions have to be re-recorded. Data is lost (stolen or corrupted). When sales files and sales reports are needed for re-checking, officers will have difficulty finding files in the master book, because they have to open the pages of the main book which are quite thick. There was a problem in September 2018 where the daily sales report was damaged by rain and the cashier had to re-record all daily transactions.